Soluble receptors for advanced glycation end-products prevent unilateral ureteral obstruction-induced renal fibrosis - Kim, Chan Ho; Kang, Hye-Young; Kim, Gyuri; Park, Jimin; Nam, Bo Young; Park, Jung Tak; Han, Seung Hyeok; Kang, Shin-Wook; Yoo, Tae-Hyun (Frontiers in Pharmacology, 2023)
Introduction: The receptor for advanced glycation end products (RAGE) and its ligands, such as high-mobility group protein box 1 (HMGB1), play an important role in the accumulation of extracellular matrix in chronic kidney diseases with tubulointerstitial fibrosis. Blocking RAGE signaling with soluble RAGE (sRAGE) is a therapeutic candidate for renal fibrosis. Methods: NRK-52E cells were stimulated with or without HMGB1 and incubated with sRAGE in vitro. Sprague-Dawley rats were intraperitoneally treated with sRAGE after unilateral ureteral obstruction (UUO) operation in vivo. Results: HMBG1-stimulated NRK-52E cells showed increased fibronectin expression, type I collagen, α-smooth muscle actin, and connective tissue growth factor, which were attenuated by sRAGE. The mitogen-activated protein kinase (MAPK) pathway and nuclear translocation of nuclear factor kappa B (NF-κB) were enhanced in NRK-52E cells exposed to HMBG1, and sRAGE treatment alleviated the activation of the MAPK and NF-κB pathways. In the UUO rat models, sRAGE significantly ameliorated the increased renal fibronectin, type I collagen, and α-smooth muscle actin expressions. Masson’s trichrome staining confirmed the anti-fibrotic effect of sRAGE in the UUO rat model. RAGE also significantly attenuated the activation of the MAPK pathway and NF-κB, as well as the increased number of infiltrated macrophages within the tubulointerstitium in the kidney of the UUO rat models. Conclusions: These findings suggest that RAGE plays a pivotal role in the pathogenesis of renal fibrosis and that its inhibition by sRAGE may be a potential therapeutic approach for renal fibrosis.